In vitro propagation of Campomanesia rufa: An endangered fruit species - Cecília Ramos de Oliveira Sant’Ana (Ciência e Agrotecnologia)
ABSTRACT The Campomanesia rufa is a fruitful species native from Brazil considered as endangered by the IUC (International Union for Conservation of Nature) and low information regarding its propagation is available. In this context, the aim of the present study was to develop in vitro germination, micropropagation and callogenesis protocols for the species. For in vitro germination, seeds were inoculated in MS medium supplemented with GA3 (gibberellic acid) and for shoot induction, the medium was supplemented with three different cytokinins BA (benzyladenine), BAP (6-Benzylaminopurine) or TDZ (Thidiazuron). For shoot growth, culture medium containing BA, BAP, TDZ were maintained under white fluorescent lamps and blue:red light-emitting diodes (LED). GA3 was also tested on in vitro shoot elongation. For oxidation control, the medium was supplemented with PVP (polyvinylpyrrolidone) and for callus induction, 2.4-D (dichlorophenoxyacetic acid). The results showed 68% germination regardless of GA3 concentration. In the propagation stage, BAP at 4.5 µM induced a higher number of shoots (4.53) and LED lamps as the light source combined with the culture medium with 1 μM BAP induced a higher number of shoots (4.08). The highest average of C. rufa length (31.9 mm) was obtained using 8.8 µM GA3. The use of PVP (584.3 uM) controls up to 27.3% oxidation in young leaf explants. The use of 10 µM 2.4-D leads to a higher callus formation (58.7 %). Therefore, it can be concluded that the use of BAP is efficient in the induction of shoots, PVP controls oxidation leaf segments, and 2.4-D induces callus in C. rufa.